2020
DOI: 10.4084/mjhid.2020.067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational interventions on psychological distress during allogeneic hematopoietic stem cell transplantation: a randomized study.

Abstract: Background Physical and psychological factors, like wrong attitudes and behaviours, can negatively influence health outcomes of the patients receiving allogeneic hematopoietic stem cell transplantation (AHSCT). Educational interventions aiming to improve knowledge on side effects, risks, complications and preventive behaviour can reduce psychological distress, and improve quality of life (QoL). We aimed to compare a standard approach with therapeutic patient education (TPE) to analyse the impact on AHSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…According to Qiao et al (2021), patient education was effective in cognitive symptom management [25]. Cioce et al (2020) have found that educational intervention was effective in terms of QoL and some symptoms experienced by patients who underwent HSCT such as anxiety and depression [31]. A study con- ducted by Sherman et al (2012) has revealed that psychoeducation plus telephone counseling was effective to improve patients' overall health, psychological well-being, and social adjustment [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Qiao et al (2021), patient education was effective in cognitive symptom management [25]. Cioce et al (2020) have found that educational intervention was effective in terms of QoL and some symptoms experienced by patients who underwent HSCT such as anxiety and depression [31]. A study con- ducted by Sherman et al (2012) has revealed that psychoeducation plus telephone counseling was effective to improve patients' overall health, psychological well-being, and social adjustment [46].…”
Section: Discussionmentioning
confidence: 99%
“…A printed booklet for educating patients was prepared after reviewing the literature [26,27,31,32]. The booklet was evaluated by 10 different professionals, namely two hematologists, four hematology nurses, and four nursing academicians.…”
Section: Interventionsmentioning
confidence: 99%
“…The material of the present study was primary based on nine articles that were further reviewed to ensure consistency with the search aim. [31][32][33][34][35][36][37][38][39] In one of these studies, the participants were all diagnosed with blood cancer, however the HSCT therapy was applied to almost one quarter (22.6%, n=42) of the total sample. This percentage was congruent with the predefined inclusion criteria, so the study was included in the final results.…”
Section: Study Selectionmentioning
confidence: 99%
“…Education on HSCT is recommended for all recipients to improve their knowledge of medication side effects, risks and complications[ 92 ]. These educational interventions enhance patients and their families’ knowledge about HSCT, reduce anxiety and depression and increase QOL[ 92 ].…”
Section: Psychosocial Interventions and Support For Hsct Patientsmentioning
confidence: 99%
“…Education on HSCT is recommended for all recipients to improve their knowledge of medication side effects, risks and complications[ 92 ]. These educational interventions enhance patients and their families’ knowledge about HSCT, reduce anxiety and depression and increase QOL[ 92 ]. In a recent qualitative study, patients expressed a desire for additional education about late complications and post-BMT QOL because they felt that complications were often unexpected, with profound negative effects on their QOL and recovery[ 93 ].…”
Section: Psychosocial Interventions and Support For Hsct Patientsmentioning
confidence: 99%